Mathematical modeling and numerical calculation of forced vibrations of piezoceramic spherical segment - Kudzinovs’ka, I.P. (Carpathian Mathematical Publications, 2014)
Vibrations of a piezoceramic segment polarized along the thickness, which are excited by a harmonically time-varying difference of potential, are considered. The corresponding solution of a two-dimensional electroelasticity problem is searched in the form of Legendre polynomial expansions in combination with the power series method. The frequency spectrum and corresponding mode kinematics for the first three values of Legendre polynomial indices are investigated. Special attention is paid to the behavior of the characteristics under studying in the area of main thickness resonance.